System Performance Characteristics of Darrieus Turbine with Tilted Blades in Current and Wave Conditions - Suyanto, Eko Marta; Fitri, Sutopo Purwono; Erwandi, Erwandi; Rahuna, Daif; Kasharjanto, Afian (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Indonesia has abundant sources of renewable energy from ocean currents and waves, or a mixture of currents and waves at certain times to be used as an energy source for power plants. So at the Indonesian Hydrodynamics Laboratory, a study has been carried out to determine the performance of the Darrieus-type vertical axis turbine model to utilize the energy of ocean currents and waves. But the Darrieus Turbine with the turbine blades positioned perpendicular to the turbine axis cannot rotate if there is only wave force. Then several turbine models were made with the placement of the blades in an inclined position, to produce optimal rotor rotation in current conditions or a mixture of currents and waves. This paper describes the testing of 3 turbine models by varying the angle of inclination of the turbine blades (45°, 60°, and 75°), but still having the same turbine rotor area and giving different input currents and wave periods to produce the best efficiency and rotation in absorb current energy or a mixture of current and wave energy. The test results show that the 3 models of slanted blade turbines can absorb both wave and current energy, but turbines with 75° blade inclination produce the best performance compared to the others when exposed to currents and waves